Bahasa daerah di ambang kepunahan: Krisis tanggung jawab bersama - Dzakiyah, Nadiyatudz (Maliki Interdisciplinary Journal, 2025)
Regional languages are an important part of cultural heritage and play a vital role in shaping the identity of a society. However, in recent generations, many regional languages in Indonesia have seen a decline in the number of speakers and are now at risk of extinction. This article discusses the lack of shared responsibility as a major factor accelerating this decline. It highlights the limited active involvement of key stakeholders such as families, schools, communities, and digital media in preserving the existence of regional languages. Each of these elements plays a crucial role in maintaining the use of these languages in daily life. The article emphasizes that language preservation should not be seen as the government’s responsibility alone, but as a collective effort involving all sectors of society. Through collaboration and shared awareness, regional languages can continue to thrive and be passed on to future generations.